Causes and consequences of cardiac fibrosis in patients referred for surgical aortic valve replacement - Galat, Arnault (ESC Heart Fail, 2019)
AIMS: Cardiac fibrosis is associated with left ventricular (LV) remodelling and contractile dysfunction in aortic stenosis (AS). The fibrotic process in this condition is still unclear. The aim of this study was to determine the role of both local and systemic inflammation as underlying mechanisms of LV fibrosis and contractile dysfunction. The diagnostic values of 2D‐strain echocardiography and serum biomarkers in the evaluation of cardiac fibrosis in this condition were assessed through correlation analyses. METHODS AND RESULTS: Patients with AS referred for surgical valve replacement were prospectively and consecutively included. They all had a comprehensive echocardiography including 2D strain. Blood samples were collected to measure cytokines and inflammatory biomarkers using Luminex bead‐based assays. A per‐surgical myocardial biopsy of the basal antero‐septal segment (S1) was performed. Serial sections of each biopsy were stained with Sirius red. Digital image analysis was used to quantify fibrosis. Immunostainings using specific antibodies against macrophage, glycoprotein (gp) 130, and interleukin 6 (IL‐6) were also performed. Patients were divided into tertiles reflecting the severity of fibrosis: mild, moderate, and severe load (TF1 to TF3). The mean age of the 58 included patients was 73 ± 11 years. Twenty‐four (43%) were in New York Heart Association III–IV. Mean aortic valve area was 0.8 ± 0.2 cm(2). Mean aortic stenosis peak velocity and mean gradient were respectively 4.5 ± 0.8 m/s and 54 ± 15 mmHg. The mean LV ejection fraction was 54 ± 12%, and the global LV longitudinal strain was −15 ± 4%. The mean S1 strain, corresponding to the biopsied region, was −10 ± 6% and was strongly correlated to fibrosis load (R = 0.83, P < 0.0001). TF3 was associated with higher mortality (P = 0.009), higher serum C‐reactive protein and IL‐6, and lower gp130 compared with the other tertiles (P < 0.05). IL‐6 and gp130 were expressed in the heart and respectively in the plasma membrane of macrophages and in the cytoplasm of both macrophages and cardiomyocytes. During follow‐up, three patients died and were all in the third fibrosis tertile. CONCLUSIONS: We found a positive correlation between elevated inflammatory markers and degree of fibrosis load. These two parameters were associated with worse outcomes in patients with severe AS. Our results may be of interest especially in patients for whom a transcatheter aortic valve implantation is indicated and myocardial biopsy is not possible. Strategies aiming at preventing inflammation might be considered to decrease or limit the progression of cardiac fibrosis in patients followed for AS.